The Effect of Service Quality and Customers’ Satisfaction toward Loyalty of Customers at Cafe Bro & Sis Bengkulu City - Septiana Sari; Ratnawili Ratnawili (Journal of Indonesian Management, 2021)
This study aimed to determine the effect of service quality and customers’ satisfaction toward loyalty of customer at Cafe Bro & Sis Bengkulu City. The object of this study were visitors at Cafe Bro & Sis Bengkulu City, totaling 96 people. The data was collected by using observation and questionnaire. The data analysis technique of this study used instrument tests, classical assumption tests, analysis of respondents' responses, multiple linear regression analysis, determinant coefficients, and also hypothesis testing. The result of the study show that in line with the results of multiple linear regression, the regression equation is obtained as follows: Y= 5.158 + 0.134 (X1) + 0.850 (X2). The variable Customer Satisfaction (X1) shows t count > t table (2.061 >1.98580 ) with a significant level (0.042 < 0.050), and the Service Quality variable (X2), showing tcount>ttable, which is 14.925 > 1.98580 and sig < a (0.000 < 0.050). The results of the F test show the value of fcount>ftable, (124.992 > 3.099) and sig 0.000 < 0.050. Based on the finding above can be concluded that service quality and customers’ satisfaction partially or simultaneously effect toward loyalty of customers at Cafe Bro & Sis Bengkulu City.